Techno-economic analysis for the production of 2,3-butanediol from brewers’ spent grain using pinch technology - Mailaram, Swarnalatha; Narisetty, Vivek; Ranade, Vivek V.; Kumar, Vinod; Maity, Sunil K. (American Chemical Society, 2022)
2,3-Butanediol (BDO) is a versatile platform chemical with great potential as the precursor for various value-added derivatives across different industrial sectors. This work thus presents a techno-economic feasibility study for microbial BDO production from C5 and C6 sugars derived from brewers’ spent grain (BSG). Water-soluble carbohydrates obtained from pretreatment were further utilized for the biogas generation. Besides, the solid residue generated after fermentation and biogas were used to generate high-pressure steam and electricity. The process integration was carried out using pinch technology for various BDO titers and plant capacities. The pinch analysis helped in the reduction of hot and cold utility consumption by about 34 and 18%, respectively. The minimum hot and cold utility consumption was 4.59 and 10.97 MW for 100 MT BSG per day with 100 g/L BDO titer, respectively. The cooling water consumption was decreased, and electricity generation was increased with the increase in BDO titer, while the BDO production cost reduced marginally. For 100 MT BSG per day, the BDO production cost was US$1.84, US$1.76, and US$1.74/kg for BDO titers of 80, 100, and 120 g/L, respectively. However, the unitary BDO production cost was only US$1.07 for 2000 MT BSG per day. For 100 g/L BDO titer, the minimum BDO selling price was US$3.63 and US$2.00/kg for 100 and 2000 MT BSG per day, respectively, with 8.5% return on investment and 5 years as the payback period.
Keywords: Fermentation; Carbohydrates; Hydrolysis; Manufacturing; Water